2011
DOI: 10.1002/spe.1001
|View full text |Cite
|
Sign up to set email alerts
|

The use of search‐based optimization techniques to schedule and staff software projects: an approach and an empirical study

Abstract: SUMMARYAllocating resources to a software project and assigning tasks to teams constitute crucial activities that affect project cost and completion time. Finding a solution for such a problem is NP-hard; this requires managers to be supported by proper tools in performing such an allocation. This paper shows how search-based optimization techniques can be combined with a queuing simulation model to address these problems. The obtained staff and task allocations aim to minimize the completion time and reduce s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 35 publications
0
36
0
1
Order By: Relevance
“…Abdel-Hamid [1] developed a system dynamics model for staffing estimation, and applied the model in NASA's DE-A project to analyze the decision of allocating up to 8 people in one team. Antoniol and his colleagues exploited queuing simulation [5] along with multi-objective optimization [63], and found that 46 was the optimal staffing level for a large maintenance project.…”
Section: More Useful Discoveriesmentioning
confidence: 99%
See 2 more Smart Citations
“…Abdel-Hamid [1] developed a system dynamics model for staffing estimation, and applied the model in NASA's DE-A project to analyze the decision of allocating up to 8 people in one team. Antoniol and his colleagues exploited queuing simulation [5] along with multi-objective optimization [63], and found that 46 was the optimal staffing level for a large maintenance project.…”
Section: More Useful Discoveriesmentioning
confidence: 99%
“…In fact, search-based approaches [1,5,63] provide dynamic restaffing capabilities so that managers can better allocate project resources at different stages of the software life cycle.…”
Section: More Useful Discoveriesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the SPSP is particularly challenging when the project is large. The space of possible allocations of employees to tasks is enormous, and providing an optimal allocation of employees to tasks becomes a very difficult task [14]. It is impractical to use exact methods to solve medium or large SPSP instances.…”
Section: Introductionmentioning
confidence: 99%
“…It is impractical to use exact methods to solve medium or large SPSP instances. Evolutionary algorithms have been employed to solve the SPSP [1], [5], [12], [14], [16], [17]. Other metaheuristics have also been used, such as ant colony optimization and its variants [4], [6], [15].…”
Section: Introductionmentioning
confidence: 99%